Singhiella simplex (singh) (hemiptera: aleyrodidae), a new aleyrodid invasive species for Colombia - Kondo, Takumasa; Evans, Gregory (ResearchGate, 2025)
Singhiella simplex is native to the Oriental region, where it is known from Burma, China and India; and has been introduced to the USA (Florida) and Puerto Rico (Hodges 2007; Evans 2008; Mannion et al. 2008). More recently, S. simplex have been recorded also from Jamaica, Brazil, Cayman Islands (Jesus et al. 2010 and Velasco et al. 2011) and was observed in Israel in 2011 (unpublished). This is the <U+FB01>rst record of S. simplex from Colombia.